Impact of Service Quality Variables Regarding the Decision Making Process: Case Study of Staying at a Youth Hostel in Surabaya - Muchammad Ilham Syaifullah A. M; Mahjudin Mahjudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Fluctuations in the number of hotel guests which tend to decrease encourage managers to further improve management performance so that things that influence the decline can be identified and then implemented as appropriate strategies to overcome them. Consumers or guests in this case are a heterogeneous community who come from various backgrounds, characteristics, habits, regions, cultures and economic levels. Based on several theories, previous research and the phenomenon of this problem, research was conducted to analyze the influence of service quality on consumers' decisions to stay at the Surabaya Youth Hostel. In research that wants to see the influence of tangible, reliability, responsiveness, assurance, empathy on the decision to stay at the Surabaya Youth Hostel. By using tabulated data from the results of a population survey with a sample of 40 respondents, visitors staying at the Surabaya Youth Hostel were analyzed. using multiple linear regression analysis tools, it can be seen. The R value of 0.951 means that the relationship between the independent variables tangible, reliability, responsiveness, assurance, empathy on consumer decisions to stay overnight is close and strong. This is indicated by an R value above 50%, namely 95.1%. The simultaneous determination value (R square) is 0.904, meaning that variations in tangible, reliability, responsiveness, assurance, empathy regarding consumer decisions to stay overnight change by 90.4% while the remaining 9.6% is influenced by other variables not studied. In this research, it can be seen that the variables tangible, reliability, responsiveness, assurance, empathy influence simultaneously (simultaneously) on the decision to stay by producing an Fcount value of 64,219 and a Ftable of 2.4 with a df in the numerator of 5 and the denominator of 34. By using the test t can be seen that all independent variables, including tangible, reliability, responsiveness, assurance, empathy, have a partial influence on the decision to stay, where reliability with a calculated t coefficient value of 4,877 is the variable that has the most influence on the decision to stay.